2010
DOI: 10.1055/s-0029-1240884
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Synephrine andβ-Phenethylamine on Humanα-Adrenoceptor Subtypes

Abstract: Synephrine and beta-phenethylamine, two naturally occurring compounds, are structurally related to ephedrine. In this study, the effects of synephrine and beta-phenethylamine on alpha-adrenergic receptor (alpha-AR) subtypes are investigated in human embryonic kidney (HEK293) or Chinese hamster ovary (CHO) cells, and compared to that of 1R,2S-norephedrine. The rank order of binding affinities was found to be the same for the subtypes tested (alpha(1A)-, alpha(2A)-, and alpha(2C)-AR) viz, 1R,2S-norephedrine > be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 16 publications
0
48
1
Order By: Relevance
“…We found that PEA is able to displace [ (Ma et al, 2010). Based on this result, we then used a functional assay to show that PEA could selectively reverse a 1 -adrenoceptor-mediated increases in vascular tone.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We found that PEA is able to displace [ (Ma et al, 2010). Based on this result, we then used a functional assay to show that PEA could selectively reverse a 1 -adrenoceptor-mediated increases in vascular tone.…”
Section: Discussionmentioning
confidence: 96%
“…a 2 -adrenoceptors expressed in Chinese hamster ovary cells (K i ∼8 mM; Ma et al, 2010). The a 2 -adrenoceptor antagonist rauwolscine also increased nerve-mediated vasoconstriction in the perfused mesenteric bed and has previously been shown to act as a sympathomimetic agent by increasing noradrenaline outflow in the vasculature (Rump et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…41) The cardiovascular effects of m-synephrine and p-synephrine were clearly distinct as a result of their markedly different adrenergic receptor binding activities, with m-synephrine exerting markedly greater binding to various α-receptor subtypes as well as β-1 and β-2 receptors. 9,[42][43][44] The well documented cardiovascular effects of m-synephrine cannot therefore be extrapolated to p-synephrine and bitter orange extract. So Stohs et al indicated that receptor binding studies involving tissues indicate that exhibits poor binding affinities or non-specificities for α-adrenoreceptor subtypes as well as β-1 and β-2 adrenoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…7,8) And p-synephrine was likely also to be binding to α-as well as β-1 and β-2 adrenoreceptors resulted in cardiovascular effects including increased cardiovascular contractility, heart rate and bronchodilation. 9,10) However, Stohs et al indicated that receptor binding studies involving tissues from humans and animals indicate that psynephrine exhibits poor binding affinities or non-specificities for α-adrenoreceptor subtypes as well as β-1 and β-2 adrenoreceptors. 11) Neuromedin U2 receptor (NMU2R), one of the two neuromedin U (NMU) receptors, was G protein-coupled receptors (GPCRs) formerly known as "orphan" receptor FM3/GPR66 and FM4.…”
Section: -4)mentioning
confidence: 99%
“…m-Synephrine does not occur in nature, is not present in BOEs, 44 and is not permitted in dietary supplements. Ma et al 45 concluded that p-synephrine acts as an antagonist, rather than an agonist, with respect to human α 2A -and α 2C -adrenergic receptors. Jordan et al 46 concluded that p-synephrine bound to β 1 -and β 2 -adrenergic receptors about 10,000-fold less actively than norepinephrine.…”
mentioning
confidence: 99%